Thermal load models for the static design of steel-concrete composite girders. (May 2023) - Wang, Ruizheng; Ji, Wei; Li, Xitong; Peng, Kai; Peng, Chen; Wang, Changhao
Abstract: Although the recommended temperature gradient models of composite girders are considered in current specifications for classifying temperature effects in various countries, they are not appropriate enough for static design. Moreover, existing national standards cannot explain the mechanism of the thermal effect on the bridge. To further investigate thermal load models of composite girders, this work proposed a decomposing method for vertical nonlinear temperature gradients based on thermal effects and a calculating method for the thermal stress of composite girders. Equivalent temperature (equivalent uniform temperature, equivalent linear temperature, and equivalent nonlinear temperature), temperature difference, and cyclic equivalent uniform temperature are analyzed to reflect the characteristics of thermal effect in composite girders. The stand values of temperature differences and equivalent temperature with a 50-year return period were investigated via probabilistic statistical analysis. Additionally, two vertical thermal load models (VTLM Ⅰ and VTLM Ⅱ) were set up to facilitate the design and applied to stress analysis. The result demonstrates that the proposed thermal load model is more suitable than the Chinese Specification for calculating the thermal effects of composite girders.